Morphological, craniodental, and molecular characterization of Platyrrhinus guianensis (Chiroptera, Phyllostomidae) and second record for Brazil - Amanda C. da S. Lima; Samira B. Mendes; Ana P. M. Olímpio; Fábio H. S. Cardoso; Cleison L. da S. Costa; Elmary da C. Fraga; Maria C. Barros; Iracilda Sampaio (Iheringia: Série Zoologia)
ABSTRACT The genus Platyrrhinus Saussure, 1860 is one of the most speciose within the Phyllostomidae family in the Neotropical region, with 19 documented species worldwide, nine of which are found in Brazil. Platyrrhinus guianensis Velazco and Lim, 2014 was first recorded in the Guiana Shield, followed by a record in the Brazilian Amazon. This study represents the second record of P. guianensis in Brazil, specifically in the Maranhão (MA) Amazon biome (Turiaçu/MA - 01°39’36”S and 45°22’12”W). Morphological, craniodental, and molecular characters were employed for species identification. The specimen exhibited a dark brown dorsal fur, a conspicuous wide and white dorsal stripe, dark gray ventral fur, a forearm length of 38.5 mm, a short skull without a fossa in the scaly root of the zygomatic arch, with two stylar cusps on the posterior crest of the upper second premolar, one stylar cusp on the anterior crest of the lower second premolar, and upper internal incisors bilobed and convergent. Molecular results supported the morphological identification, confirming the occurrence of P. guianensis in the Maranhão Amazon. Molecular results provide the first public sequence of P. guianensis for the 16S rRNA gene and a new sequence for the COI gene, which will be useful in future studies for the species. These results supported the morphological identification, confirming the occurrence of P. guianensis in the Maranhão Amazon. This record extends the known distribution of this species approximately 1428.32 km to the east within the Amazon biome in Brazil.